Handbook of forensic sociology and psychology - Goldstein, Mark L.; Morewitz, Stephen J. (Springer New York, 2014)
Since their emergence as social sciences, psychology and sociology have found a natural home in the justice system. And while the term forensics often translates into CSI scenarios in the public imagination, the bulk of the work takes place in the courtroom, where lawyers, judges, and jurors rely on psychology and sociology experts for aid in decision making.  The Handbook of Forensic Sociology and Psychology offers comprehensive, straightforward coverage of the impact of social science on the spectrum of civil and criminal legal issues. This unique reference guides readers through the work of professionals in both fields as expert witnesses, as consultants before and during trials, and in critiquing legal and law enforcement procedure. Offering expert insights into the making and breaking of laws, contributors analyze forensic psychology and sociology theories and methods used in areas as diverse as immigration, divorce and family, product liability, and employment and education related litigation. A range of evaluative procedures, from custody to competency, child abuse to the death penalty, is examined as well. Other topics featured in the Handbook include:  The problem of interrogation-induced false confession. The role of the gang expert in court. Gender analysis in military court-martials. Sociological theory and methods in suicide litigation. Psychosocial theories about anger and their relevance in litigation. Neuropsychological testing standards and ethics. The Handbook of Forensic Sociology and Psychology opens out this increasingly important field for criminologists, and gives researchers in forensic psychology and sociology clear insights into challenges and opportunities facing these fields.